Formation of filamentous fungal pellets in aerobic granular sludge via reducing temperature and dissolved oxygen: Characteristics of filamentous fungi and denitrification performance. (July 2021) - Liu, Xiaoying; Li, Renjie; Chen, Rui; Chen, Yuan; Zeng, Ao; Deng, Yibin; Ma, Jinxia; Chen, Ming
Graphical abstract: Highlights: The growth of filamentous microorganisms in SBR was induced due to low temperature and DO. The relationship between SVI and change of filamentous microorganisms was revealed. The formation of fungal pellets prompted the denitrification performance of AGS. The fungal Bradymyces and Knufia were isolated from filamentous pellets. Abstract: A lab-scale sequencing batch reactor (SBR) using glucose as carbon source was operated for 500 days to investigate the formation of filamentous organisms and their function on stability of AGS system. After 250 days' stable operation under conditions of 25 ± 2 °C and dissolved oxygen (DO) of 4–5 mg/L (stage I), the temperature and DO were reduced to 10 ± 2 °C and DO of 1–2 mg/L until 280 days (stage II), to induce the growth of filamentous microorganisms. After that until 500 days (stage III), overgrowth of filamentous microorganisms with relative abundances of up to 19.46%, formation of black filamentous fungal pellets, and reconstruction of AGS granules were observed in turn. The relation between settling of AGS (SVI 30–72 mL/g) and filamentous microorganisms was revealed. Filamentous pellets were purified and identified as fungal Bradymyces and Knufia, with stronger denitrification performance on nitrite than nitrate. The results indicated that filamentous fungal pellets contributed to good sludge settling performance and promoted the denitrification process in AGS.